2005
DOI: 10.1021/cm0519380
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Low-Temperature Reduction Behavior of the CeO2−ZrO2−Bi2O3 Solid Solution by Addition of Silver

Abstract: Low-temperature reduction behavior of a CeO2−ZrO2−Bi2O3 solid solution was promoted by the addition of silver, which is an oxygen permeable component. The reactivity of oxygen in the bulk of the catalyst highly improves the soot combustion activities at low temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 24 publications
1
19
1
Order By: Relevance
“…Our studies have shown that the introduction of a trace amount of Bi 2 O 3 within the CeO 2 -ZrO 2 lattice was effective in promoting the reduction behavior of the Ce x Zr 1-x O 2 materials at low temperatures below 300°C. [8][9][10] Since the addition of precious metal particles on the surface of the mixed oxides was shown to be critical in lowering the reduction temperature, the amount of such precious metals employed in the automotive catalysts has increased drastically over the last decade, reflecting the growing strength of worldwide emission regulations. [11,12] Consequently, it is of great urgency to develop new materials that can reduce or eliminate the amount of precious metals in automotive exhaust catalysts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies have shown that the introduction of a trace amount of Bi 2 O 3 within the CeO 2 -ZrO 2 lattice was effective in promoting the reduction behavior of the Ce x Zr 1-x O 2 materials at low temperatures below 300°C. [8][9][10] Since the addition of precious metal particles on the surface of the mixed oxides was shown to be critical in lowering the reduction temperature, the amount of such precious metals employed in the automotive catalysts has increased drastically over the last decade, reflecting the growing strength of worldwide emission regulations. [11,12] Consequently, it is of great urgency to develop new materials that can reduce or eliminate the amount of precious metals in automotive exhaust catalysts.…”
mentioning
confidence: 99%
“…250-316°C. [8][9][10] It is important to note that reduction behavior below 100°C, even after calcination at 1000°C, has never been attained in conventional catalysts in the absence of precious metals. Following the TPR measurements for CZB/Al 2 O 3 , the formation of CeAlO 3 and phase segregation of CeO 2 , ZrO 2 , or Bi 2 O 3 were undetectable.…”
mentioning
confidence: 99%
“…In our laboratory, investigations have focused on novel materials that can supply reactive oxygen molecules not only from the surface but also from the bulk, in order to develop a new oxide catalyst that can completely oxidize hydrocarbons, including ethylene, at low temperatures. As a result, it was found that CeO 2 ZrO 2 Bi 2 O 3 solid solutions exhibit novel oxygen storage and release properties from those of conventional CeO 2 ZrO 2 solid solutions 15–17. Furthermore, we demonstrated that a Ce 0.64 Zr 0.16 Bi 0.20 O 1.90 (20 wt%)/γ‐Al 2 O 3 (CZB/Al 2 O 3 ) solid has remarkable oxygen storage and release abilities at low temperatures 18,19.…”
Section: Advanced Oxidation Catalysts Of Vocsmentioning
confidence: 78%
“…It has been reported that CeO 2 ZrO 2 solid solutions have high oxygen storage and release properties at moderate temperatures around 500°C,21–23 but there are no reports of oxide materials that can exhibit redox properties at 100°C. We found that the introduction of small amounts of Bi 2 O 3 within the CeO 2 ZrO 2 lattice was quite effective in promoting the reduction of CeO 2 ZrO 2 materials at temperatures below 300°C 15–17. The reasons why Bi 2 O 3 was chosen as the third component were: (i) both Bi 2 O 3 and Bi 2 O 3 R 2 O 3 (R = Y, LaYb) solid solutions show a considerably high oxide anion conductivity,24–26 (ii) Bi 2 O 3 is easily reduced to release oxygen, and (iii) oxygen vacancies have to be produced within the lattice to maintain charge compensation because Bi 3+ has lower valence (trivalent) than Ce 4+ and Zr 4+ (tetravalent).…”
Section: Advanced Oxidation Catalysts Of Vocsmentioning
confidence: 99%
“…Recently, Bi 2 O 3 -based systems mixed with other oxides have attracted increasing attention, such as Bi-Ln-O (Ln representing rare earth elements) [4,5], Bi 10 Mo 3 O 24 [6], MBi 6 V 2 O 15 (M = Pb, Sr, Ca, Cd, etc.) [7], Bi 2 O 3 -HfO 2 -Y 2 O 3 [8] and Bi 2 O 3 -CeO 2 -ZrO 2 [9]. High ionic conductivity and good thermal stability have been observed in these compounds.…”
mentioning
confidence: 93%